Determination of Mirabegron in rat plasma by UPLC–MS/MS after oral and intravenous administration - Chen,Lingdi (2019)
SUMMARY Mirabegron is a kind of β3 adrenergic receptor agonist which is an effective drug for the treatment of overactive bladder. In this research, a UPLC–MS/MS method is developed and validated for the study of mirabegron pharmacokinetic in rats. A protein precipitation method is applied for sample preparation with acetonitrile. m/z 397.3→379.6, m/z 326.4→121.0 for mirabegron, tolterodine (IS), respectively in the positive ion mode was performed for quantitation. The method is reliable and reproducible in our study (intra-day precision≤11.06%, inter-day precision≤11.43%) with concentration curves linear from 5 to 2500 ng/mL(R2>0.999). Stability studies demonstrated that mirabegron was stable under a variety of storage conditions. This method was successfully applied for determining mirabegron in rats after oral and intravenous administration.